Peanut Skin Extract Attenuates Doxorubicin Induced Myocardial Infarction by Alleviating Cardiac Inflammation, Oxidative Stress and Histological Changes in Wistar Rats - Wasim, Mohd; Khan, Aamir; Iqubal, Ashif; Haque, Syed Ehtaishamul (Indian Journal of Pharmaceutical Education and Research)
Background: Cancer treatment is a major global concern. The anticancer drugs being used are effective, but their uses are curtailed due to ground: toxicity that they produce. Doxorubicin is one of the most efficient anti-cancer drugs, but its usage is also restricted due to cardio toxicity. Hence the demand of a drug is always there which can reduce toxicity and be used along with doxorubicin, thereby safeguarding myocardium during cancer treatment. Objectives: Thinking in the same direction we tried to evaluate Peanut Skin Extract (PSE) for its cardio protective potential in doxorubicin challenged rats. Materials and Methods: Seven groups of rats having six animals per group were divided into Vehicle control; Doxorubicin (DOX 2 mg/kg/48 hr)+PSE 300+DOX 2 mg/kg/48 hr; PSE 400+DOX 2 mg/kg/48 hr; Fenofibrate (FF 80)+DOX 2 mg/kg/48 hr; PSE 400 per se; and FF 80 per se. Dosing was done for 12 days. Animals were sacrificed on 13th day and biochemical parameters of oxidative stress and inflammation were estimated. Histopathological analysis was also performed to establish cardioprotective effect of peanut skin extract. Results: In our study it was found that peanut skin extract behaved as a potential cardioprotective candidate that attenuated DOX- induced cardiotoxicity. Conclusion: Thus, based on the above study we came to the conclusion that peanut skin extract protects doxorubicin-induced myocardial damage.
Keywords: Peanut skin extract; Inflammation; Doxorubicin; Myocardial infarction; Oxidative stress.